FUN WORKPLACE: HOW TO CREATE AND WHAT IS THE BENEFITS - Fadillah Ismail; Siti Sarawati Johar; Chan Shiau Wei (Journal of Islamic, Social, Economics and Development, 2023)
Having fun at work is essential to employee motivation, creativity and able to work together effectively. It is something that can and ought to be included into every workday. Having fun at work is beneficial for all kinds of teams, even those that are hybrid or remote. Companies that put an emphasis on employee happiness, particularly when it's linked with career advancement, have happier workers and more productive workers as a consequence. The objective of this paper is to discuss on how to create fun workplace and the benefit of it. To highlight, this study will discuss several ways of creating fun workplace which is socializing with workers, be a great communicator and no secrets and lastly, being gratitude. There are also benefits of creating fun workplace including high quality relationship between workers, ease emotional labor and increase employee retention. Besides, there are two challenges in creating fun workplace including unwanted sexual attention and able to be creative all the time.